Ecogeomorphology and vulnerability in a Mediterranean ria-type coast (La Maddalena Archipelago, NE Sardinia, western Mediterranean). Issue 2 (1st December 2021) - De Muro, Sandro; Buosi, Carla; Biondo, Manuela; Ibba, Angelo; Ruju, Andrea; Trogu, Daniele; Porta, Marco
ABSTRACT: This paper presents a map describing the main geomorphological and sedimentological features, hydrodynamics, benthic habitat distributions and human impact on the coastal and marine areas of the Archipelago of La Maddalena (NE Sardinia, western Mediterranean). This cartography is based on an interdisciplinary sea-land approach, with the aim being to support sustainable and successful beach management in the face of a changing climate and environment, thereby contributing to the achievement of the Agenda 2030 Sustainable Development Goals (13, 14 and 15). In the Main Map (1:14, 000 scale), the static and dynamic features of the beach systems and adjacent inner shelf are divided into thematic sections that include the geomorphological elements, hydrodynamics, sedimentological distributions, benthic habitat (mainly Posidonia oceanica meadow) and anthropogenic impacts. The map establishes a fundamental, multidisciplinary benchmark that is able to provide substantial scientific support to policymakers in relation to future vulnerability-assessment activities and the definition of land-management strategies.